Edible Fish Powder from Small Sized Indian Major Carps - A.K., Chattopadhyay; B., Madhusudana Rao; Gupta, Sibsankar (Fishery Technology, 2025)
A new product in the form of edible fish powder was developed from small sized Indian Major Carps by utilizing these fish at the time of glut. Small sized rohu, catla and mrigal were converted to nutritionally rich edible fish powder by thermal processing, without deboning the fish. Freshly prepared edible fish powders from rohu, catla and mrigal were rich in protein (67.4 to 72.6%) and minerals like calcium (1213 to 1344 mg%) and phosphorus (1770 to 1934 mg%). Water activity (aj of edible fish powders was low. The fresh ediblfe fish powders were negative for the presence of E.coli, coagulase +ve Staphylococci and Yeast & mould. The powder made from rohu was acceptable up to 4 months and the powder made from catla was acceptable up to 5 months (maximum period tested) of storage in 200 gauge HDPE at room temperature. Sensory quality of edible fish powders made from rohu and catla (both fresh and at monthly storage intervals) used at 10% level was found acceptable.